2021
DOI: 10.3390/ijms22179559
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentanone Derivative Attenuates Memory Impairment by Inhibiting Amyloid Plaques Formation in the 5xFAD Mice

Abstract: Alzheimer’s disease (AD) is a chronic neurodegenerative disorder. This study was designed to investigate the effects of cyclopentanone derivative i.e., 2-(hydroxyl-(3-nitrophenyl)methyl)cyclopentanone (3NCP) on behavior, amyloid β (Aβ) plaque deposition, and βAPP cleaving enzyme-1 (BACE-1) expression in the 5xFAD mouse brain. In this study, computational studies were conducted to predict the binding mode of the 3NCP with target sites of the β-secretase. In vivo studies were performed on the 5xFAD mice model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…The Acacia stenophylla bark contains cyclic ketone derivatives, it has been reported that these derivatives reduce cholinesterases activities, Aβ plaques formation, neuroinflammation, and oxidative stress in the mice model of Alzheimer's disease. 30,72 The possible mechanism of action of Acacia stenophylla bark extracts to ameliorate amnesia is their anti-cholinesterase and anti-oxidant activities and the anti-inflammatory, anti-oxidant, and anti-cholinesterase properties of their active constituents derivatives. The schematic representation of ASEE and ASB extracts is shown in Figure 9.…”
mentioning
confidence: 99%
“…The Acacia stenophylla bark contains cyclic ketone derivatives, it has been reported that these derivatives reduce cholinesterases activities, Aβ plaques formation, neuroinflammation, and oxidative stress in the mice model of Alzheimer's disease. 30,72 The possible mechanism of action of Acacia stenophylla bark extracts to ameliorate amnesia is their anti-cholinesterase and anti-oxidant activities and the anti-inflammatory, anti-oxidant, and anti-cholinesterase properties of their active constituents derivatives. The schematic representation of ASEE and ASB extracts is shown in Figure 9.…”
mentioning
confidence: 99%